AL-QUR’AN KULTURAL DAN KULTUR QUR’ANI: Interaksi antara Universalitas, Partikularitas, dan Kearifan lokal - Wardani Wardani (AL-TAHRIR, 2015)
Abstract: The issue on universality and particularity of Quranic teachings becomes a central issue which has triggered serious debate among Moslem scholars since the  Qur’an, as a scripture, embodies God’s speech whose doctrines have been intended as trans-historical teachings going beyond time and space. In addition, it was revealed gradually based on the events and circumstances to respond the the social problems happening during the periods of prophecy. This article is aimed to explore some Moslem scholars on the issues of (1) identifying the ways of  Qur’an in acculturation vis-à-vis Arab tradition, (2) studying on to what extent the Quranic exegeses in Indonesia have absorbed local traditions, and (3) analyzing the modes of interaction between the Qur’an and culture. The divinity of teachings in the qu’ran did not mean that it would lose the historical nature of its contents to a certain extent, since it had been revealed for a long time in the Arabian peninsula. In Indonesia, such acculturation also emerged when some authors of Quranic exegeses, such as Bakri Syahid in his Tafsir al-Huda, used local wisdom to interpret the Qur’an, for instance, the atribution of “pepundhen” (originally means: sacred place) to God. The interaction between the Qur’an and culture could be seen from acculturation of the Qur’an resulting in the so-called “cultural Qur’an”, and from Islamization of culture resulting in the so-called “Quranic culture”. الملخص: مازالت شمولية وإقليمية تعاليم القرآن قضية جدلية أحدثت جدلا جديا بين علماء المسلمين، إذ أن القرآن ككتاب مقدس يحتوى على كلام الرب الذى كانت تعاليمه تراد أن تكون صالحة عبر التاريخ خلال الزمان و المكان، مع أنه منزل فى ظروف معينة استجابة لروح مقتضيات الزمان. وهذه المقالة تهدف إلى كشف آراء علماء المسلمين عن هذه القضية، وإلى كشف مناهج القرآن فى التثقف عند مواجهة عادات العرب، وإلى البحث عن مدى ما وصل إليه تفاسير القرآن فى إندونيسيا فى استيعاب العادات الإقليمية، و أخيرا إلى تحليل طرائق التعامل بين القرآن والثقافة. ووصلت هذه الدراسة إلى نتيجة أن شمولية القرآن تتعلق بالقيم والقواعد التى تندرج تحتها كل أحكامه الجزئية، كالعدالة والتوسط، وهما عمادا تعاليم الإسلام. و قداسة القرآن لا تعنى غياب شخصيته التاريخية إلى حد معين، إذ أنه منزل زمانا طويلا فى جزيرة العرب.  وتتمثل تاريخيته من  تعاليمه التى تظهر من خلالها كأنها تفاوض عادات العرب، كالتجارة واحترام الأشهر الحرم،  فغاية القرآن لتحويل عادة جعلته يرشح قيما تكون أسسا لأحكام، بطريق  رفض عادة أو إعادة تكوينها. وظهر مثل هذا التثقف أيضا فى إندونيسيا عند ما كان مفسرو القرآن الإندونيسيون، مثل بكري شهيد من خلال كتابه "تفسير الهدى"، يستخدمون الحكمة الإقليمية فى تفسير القرآن، كوصف الرب بفوفوندين pepundhen (تعنى لغة: المكان المقدس). Abstrak: Permasalahan seputar universalitas dan partikularitas al-Qur'an menjadi isu sentral yang telah memicu perdebatan serius di kalangan sarjana muslim karena al-Qur'an, sebagai kitab suci, melampaui waktu dan ruang. Selain itu, ia merespon masalah-masalah sosial yang terjadi selama periode kenabian. Artikel ini mengeksplorasi beberapa persoalan mengenai (1) identifikasi akulturasi al-Qur'an dengan tradisi Arab, (2) studi terhadap  tafsir al-Quran di Indonesia yang menyerap tradisi lokal, dan (3) analisis terhadap bentuk-bentuk interaksi Qur'an dan kultur. Keilahian ajaran al-Qur'an tidak berarti bahwa isi al-Qur'an kehilangan sifat historisnya karena ia diwahyukan untuk waktu yang lama di jazirah Arab. Historisitasnya tercermin dalam beberapa doktrin yang telah dinegosiasikan dengan tradisi Arab. Tujuan utamanya untuk mengubah setiap tradisi yang ada dengan menyisipkan nilai yang mendasari segala bentuk aturan atau merekonstruksi tradisi. Di Indonesia, akulturasi tersebut juga muncul ketika beberapa penulis tafsir al-Qur’an, seperti Bakri Syahid dalam bukunya Tafsir al-Huda, menggunakan kearifan lokal untuk menafsirkan al-Qur'an, misalnya, penisbatan "pepundhen" (awalnya berarti: tempat suci ) kepada Allah. Interaksi antara al-Qur'an dan budaya dapat dilihat dari akulturasi al-Qur'an sehingga disebut "al-Qur'an kultural", dan dari Islamisasi budaya menghasilkan apa yang disebut "kultur Qur'ani".Keywords: universalitas, kearifan lokal, enkulturasi, al-Qur'an kultural, kultur Qur'ani